2020
DOI: 10.1073/pnas.2008980117
|View full text |Cite
|
Sign up to set email alerts
|

Decanoic acid inhibits mTORC1 activity independent of glucose and insulin signaling

Abstract: Low-glucose and -insulin conditions, associated with ketogenic diets, can reduce the activity of the mechanistic target of rapamycin complex 1 (mTORC1) signaling pathway, potentially leading to a range of positive medical and health-related effects. Here, we determined whether mTORC1 signaling is also a target for decanoic acid, a key component of the medium-chain triglyceride (MCT) ketogenic diet. Using a tractable model system, Dictyostelium, we show that decanoic acid can decrease mTORC1 activity, under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 77 publications
0
41
0
Order By: Relevance
“…146 A limitation of the KD, however, especially in older children and adults, is that it is difficult to maintain; the recent evidence that decanoic acid reduces mTORC1 activity in model systems, including astrocytes derived from TSC patients, suggests that a more sustainable diet rich in decanoic acid may be able to produce similar results to the KD, with better compliance. 109 The EPISTOP trial should hopefully pave the way for evaluating targeted treatments that address the underlying pathophysiology of TSC in a preventative capacity, potentially including EVE and CBD. To date, EVE and CBD have been evaluated only in a conventional setting, while it is certainly valid to hypothesise that prophylactic treatment with these treatments, especially EVE, will be even more favourable than VGB due to the targeted mechanism of action, strengthened by data from some animal studies showing the benefits of early treatment with mTOR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…146 A limitation of the KD, however, especially in older children and adults, is that it is difficult to maintain; the recent evidence that decanoic acid reduces mTORC1 activity in model systems, including astrocytes derived from TSC patients, suggests that a more sustainable diet rich in decanoic acid may be able to produce similar results to the KD, with better compliance. 109 The EPISTOP trial should hopefully pave the way for evaluating targeted treatments that address the underlying pathophysiology of TSC in a preventative capacity, potentially including EVE and CBD. To date, EVE and CBD have been evaluated only in a conventional setting, while it is certainly valid to hypothesise that prophylactic treatment with these treatments, especially EVE, will be even more favourable than VGB due to the targeted mechanism of action, strengthened by data from some animal studies showing the benefits of early treatment with mTOR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“… 146 A limitation of the KD, however, especially in older children and adults, is that it is difficult to maintain; the recent evidence that decanoic acid reduces mTORC1 activity in model systems, including astrocytes derived from TSC patients, suggests that a more sustainable diet rich in decanoic acid may be able to produce similar results to the KD, with better compliance. 109 …”
Section: Discussionmentioning
confidence: 99%
“…We initially investigated the effect of CBD, CBG, CBDA and CBDV on mTORC1 signalling in D. discoideum (Figure 1a,b). We employed a western blot approach, using an antibody against the phosphorylated form of the eukaryotic translation initiation factor 4E‐binding protein 1 (4EBP1) as a direct target of mTORC1 in D. discoideum (Chang et al, 2020; Nichols et al, 2020), that is reduced in starvation and following treatment with two established mTOR inhibitors (Warren et al, 2020) (Figure 1b). Cells were treated for 1 h with each phytocannabinoid at 0.25 μM, a concentration similar to that reported in rodent brain tissue following oral dosing of CBD and in human plasma samples from clinical trials with Epidiolex® (Devinsky et al, 2018), and were analysed for phospho‐4EBP1 (p4EBP1) levels (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…as a direct target of mTORC1 in D. discoideum (Chang et al, 2020;Nichols et al, 2020), that is reduced in starvation and following treatment with two established mTOR inhibitors (Warren et al, 2020) (Figure 1b). Cells were treated for 1 h with each phytocannabinoid at 0.25 μM, a concentration similar to that reported in rodent brain tissue following oral dosing of CBD and in human plasma samples from clinical trials with Epidiolex® (Devinsky et al, 2018), and were analysed for phospho-4EBP1 (p4EBP1) levels (Figure 1c).…”
Section: Cbd and Cbg Increase Mtor Activity In Wt D Discoideum Cellsmentioning
confidence: 99%
“…However, so far, no sedative or other central nervous system side effects have yet been observed in people and dogs (see Section 5.1). Also, a recent publication found that 300 µmol·L –1 decanoic acid can block the activity of mechanistic target of rapamycin complex 1 in ex vivo rat hippocampus and in tuberous sclerosis complex patient‐derived astrocytes 135 …”
Section: Proposed Antiseizure Mechanisms Of Mctsmentioning
confidence: 99%